A comparison of instrumentation methods to estimate thoracolumbar motion in field-based occupational studies. (May 2015) - Schall, Mark C.; Fethke, Nathan B.; Chen, Howard; Gerr, Fred
Abstract: The performance of an inertial measurement unit (IMU) system for directly measuring thoracolumbar trunk motion was compared to that of the Lumbar Motion Monitor (LMM). Thirty-six male participants completed a simulated material handling task with both systems deployed simultaneously. Estimates of thoracolumbar trunk motion obtained with the IMU system were processed using five common methods for estimating trunk motion characteristics. Results of measurements obtained from IMUs secured to the sternum and pelvis had smaller root-mean-square differences and mean bias estimates in comparison to results obtained with the LMM than results of measurements obtained solely from a sternum mounted IMU. Fusion of IMU accelerometer measurements with IMU gyroscope and/or magnetometer measurements was observed to increase comparability to the LMM. Results suggest investigators should consider computing thoracolumbar trunk motion as a function of estimates from multiple IMUs using fusion algorithms rather than using a single accelerometer secured to the sternum in field-based studies. Highlights: Inertial measurement unit estimates were comparable to Lumbar Motion Monitor estimates. Use of two inertial measurement units increased comparability. Fusion of accelerometer and gyroscope measurements increased comparability.